Profil Potentially Inappropriate Medications (PIM) Menggunakan Kriteria Beers 2019 pada Pasien Geriatri Poli Penyakit Dalam RSUD Pasar Minggu Tahun 2022 - Nur Hasanah; Ros Sumarny; Roswita Roswita (CV. Green Publisher Indonesia, 2026)
Geriatric patients are elderly patients who suffer from multipathology and thus receive polypharmacy and because of changes in physiological function, the treatment they receive is potentially inappropriate. The Potential Inappropriated Medications (PIM) can be identified using the 2019 Beers Criteria. This study aims to obtain an overview of: disease, treatment and the incidence of PIM in geriatric patients in internal medicine at Pasar Minggu Regional Hospital for the period January-December 2022 so that the results Research can be used as a consideration for administering and monitoring drug therapy. This research used a descriptive method, the research subjects used total sampling according to the inclusion criteria from looking at medical records with a sample size of 281 prescription sheets. The research results of the three highest diagnoses were: Diabetes Mellitus, Hypertension and Chronic Kidney Failure, the three drugs most frequently received by patients were: Amlodipine, Metformin and Folic Acid. The PIM profile was 146 (52%) did not experience PIM events and 135 (48%) experienced PIM events. Category 1 is the category that occurs most often, namely 48% with the most frequent type of drug: Glimepiride.